Attempts and challenges: experiences with palatal memory plate utilization in children with Down syndrome: a case report study: Palatal Memory Plate in Down Syndrome children: case report - Doro, Isabela Afonso; Martins, Laís Canêdo; Machado, Fernanda Campos; Carrada, Camila Faria; Scalioni, Flávia Almeida Ribeiro (HU Revista, 2024)
Introduction: Down syndrome (DS) causes intellectual disability and craniofacial changes due to chromosomal alterations. The Palatal Memory Plate (PPM) is an effective preventive measure for orofacial hypotonicity in DS children. Involving dentists and speech therapists, this multidisciplinary treatment addresses issues like hypotonic tongue, diastasis, and tongue protrusion. Objective: Evaluate the use of PPM in DS children. Cases Report: Two children participated in the study, a 3-month-old female with no erupted teeth and a 2-year-old female with erupted teeth. After receiving professional instructions on the use, benefits, and implications of the PPM, the participants underwent digital scanning for the fabrication of the device. Mothers were guided on how to place, remove, and the recommended frequency and duration for daily use of the PPM. Throughout the monitoring period, it was found that the participants were unable to fully adhere to the recommended protocol for PPM use, due to a variety of individual factors such as difficulties in adapting to the device, personal commitments of the families, children’s health problems, and the absence of a multidisciplinary team involved in the treatment, which limited the achievement of effective results. Conclusion: Despite deviations from the prescribed protocol, the study emphasizes the need for individual adaptations and multidisciplinary teamwork. Tailoring interventions to unique patient need in DS orofacial management is crucial for comprehensive and effective care. Additionally, recognizing family challenges also aids healthcare professionals in devising strategies for a more positive experience.